Pelatihan Legislative Drafting bagi Aparat Desa Kamanasa, Kecamatan Malaka Tengah, Kabupaten Malaka - Darius Mauritsius; Simplexius Asa; Detji Kory Elianor Rooseveld Nuban (Jurnal Pengabdian Kepada Masyarakat Undana, 2026)
The Community Service Activity (PKM) aims to provide Legislative Drafting training to village officials and the Village Consultative Body (BPD) of Kamanasa Village, Malaka Tengah Sub-district, Malaka Regency, in order to improve the capacity, abilities and skills of village officials and the BPD in creating and drafting village regulations. This PKM activity was attended by the village government, BPD and community leaders who are concerned about the drafting of village regulations. The problem faced is the lack of knowledge and skills of the community in the field of law and legislation, as there are no law graduates among the village officials and BPD. The PKM activity was carried out using a training method consisting of material presentation, discussion and group work. The results of the PKM achieved by the partners were increased knowledge in the field of law and skills in drafting village regulations. Another benefit was the production of a Draft Village Regulation on Livestock Maintenance, which will create order and security for the community in raising livestock and managing plantations and yards.